2013
DOI: 10.1103/physreva.87.012302
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement signatures for the dimerization transition in the Majumdar-Ghosh model

Abstract: The transition from a gapless liquid to a gapped dimerized ground state that occurs in the frustrated antiferromagnetic Majumdar-Ghosh (or J 1 − J 2 Heisenberg) model is revisited from the point of view of entanglement. We study the evolution of entanglement spectra, a "projected subspace" block entropy, and concurrence in the Schmidt vectors through the transition. The standard tool of Schmidt decomposition along with the existence of the unique MG point where the ground states are degenerate and known exactl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For example, the entanglement entropy (EE) is given by Tr(ρ A lnρ A ) = Tr(ρ B lnρ B ). The entanglement spectrum (ES) [2] (defined as the set of eigenvalues of a fictitious entanglement Hamiltonian, H e , with ρ A written as e −H e ) is a useful tool in understanding topological states of matter and strongly correlated systems, including fractional quantum Hall (FQH) systems [2-10], quantum spin chains [11][12][13][14][15][16][17] and ladders [18][19][20][21][22][23][24][25][26], topological insulators [27][28][29][30][31][32], symmetry broken phases [33,34], and other systems in one [35][36][37][38][39] and two [40][41][42][43][44][45][46][47][48][49][50][51][52] spatial dimensions. These studies predominantly focused on real / orbital space entanglement.…”
mentioning
confidence: 99%
“…For example, the entanglement entropy (EE) is given by Tr(ρ A lnρ A ) = Tr(ρ B lnρ B ). The entanglement spectrum (ES) [2] (defined as the set of eigenvalues of a fictitious entanglement Hamiltonian, H e , with ρ A written as e −H e ) is a useful tool in understanding topological states of matter and strongly correlated systems, including fractional quantum Hall (FQH) systems [2-10], quantum spin chains [11][12][13][14][15][16][17] and ladders [18][19][20][21][22][23][24][25][26], topological insulators [27][28][29][30][31][32], symmetry broken phases [33,34], and other systems in one [35][36][37][38][39] and two [40][41][42][43][44][45][46][47][48][49][50][51][52] spatial dimensions. These studies predominantly focused on real / orbital space entanglement.…”
mentioning
confidence: 99%
“…In the second group, which is most relevant to the research in this work, only the ground states (GSs) of the Hamiltonian can be obtained. For example, in the most representative spin-1/2 Majumdar–Ghosh (MG) model 24 29 , which reads as with This model can be obtained from the Fermi-Hubbard by second-order exchange interaction, thus for anti-ferromagnetic interaction. The GSs of the above model can be expressed exactly as the product of singlet dimers.…”
Section: Introductionmentioning
confidence: 99%
“…However, author Min-Fong Yang [22] have shown that in general onset of QPT need not necessarily be detected by concurrence, block entropy or by any other entanglement measure. The Majumdar-Ghosh model is an extensively studied spin chain model, and a plethora of research articles has been written on the entanglement study of the Majumdar-Ghosh model [23][24][25].…”
Section: Introductionmentioning
confidence: 99%